System Dynamics Simulation and Analysis of Water Resources Utilization in Longkou City,Shandong Province - YANG Xiao; LIU Xinyu; QIN Huanhuan (Renmin Zhujiang)
Based on system dynamics analysis method,this paper predicts and analyzes the comprehensive utilization and development of water resources in Longkou City,Shandong Province from 2019 to 2050 under four different scenarios.The results show that:①The water demand of Longkou City increases with the forecast time.In the forecast period,the average total water demands of Longkou City under the four scenarios are 13.726,15.078,11.307 and 13.944 billion m3,respectively.At the end of the forecast period (2050),the total water demands of Longkou City under the four scenarios are 18.392,24.271,15.975 and 22.468 billion m3 respectively;②The water shortage under different scenarios is different.The proportion of water shortage years in the forecast period is 91.18%,91.18%,50.00% and 67.65%,respectively.The average water shortage volume is 2.886,4.158,0.610 and 3.091 billion m3 respectively,and the average water shortage index is 0.209 6,0.258 9,0.175 3 and 0.282 9 respectively;③ Adhering to the concept of environmental protection and sustainable development,it is necessary to balance the water conservation and social and economic development in the future development of Longkou City.Through the analysis and comparison of the simulation results,the comprehensive development scenario is the best among all scenarios for resource exploitation and social and economic sustainable development.